Physical workload, long-term sickness absence, and the role of social capital. Multi-level analysis of a large occupation cohort - Eszter Török; Alice Jessie Clark; Annette Kjær Ersbøll; Jakob Bue Bjorner; Andreas Holtermann; Reiner Rugulies; Anthony D LaMontagne; Allison Milner; Naja Hulvej Rod (Nordic Association of Occupational Safety and Health (NOROSH), 2020)
OBJECTIVES: This study determined the prospective relation between physical workload and long-term sickness absence (LTSA) and examined if work-unit social capital may buffer the effect of high physical workload on LTSA. METHODS: We included 28 925 participants from the Danish Well-being in HospitAL Employees (WHALE) cohort, and followed them for two years. Physical workload and social capital were self-reported and categorized into low, medium, and high. Physical workload was analyzed on the individual level, whereas social capital was analyzed on the work-unit level. LTSA data were obtained from the employers' payroll system. We performed two-level logistic regression analyses: joint-effect and stratified analyses adjusted for baseline covariates. RESULTS: High versus low physical workload was associated with a higher risk of LTSA [odds ratio (OR) 1.55, 95% confidence interval (CI) 1.40-1.72]. There was a multiplicative interaction (P=0.007) and a tendency of sub-additive interaction [relative excess risk due to interaction (RERI) -0.49, 95% CI -1.03-0.06] between physical workload and social capital. Doubly exposed employees had the highest risk of LTSA (OR 2.45; 95% CI 2.02-2.98), but this effect was smaller than expected from the sum of their main effects. CONCLUSIONS: We found a prospective relation between physical workload and LTSA but no evidence of high social capital buffering the effect of high physical workload. High physical workload was a risk factor for LTSA at all levels of social capital and employees exposed to both exposures had the highest risk of LTSA. Interventions should aim at both improving social capital and reducing physical workload in order to efficiently prevent LTSA.